The Influence of Mineral-Based Compound Fertilizer (CFC) on the Health and Production of Tea Plant Clone GMB 7 - Eko Pranoto; Ridwan Saleh; Restu Wulansari (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
Tea is a commodity that has a significant contribution to Indonesia’s foreign exchange, especially from non-oil and gas sectors. Fertilization is one of the important factors to produce high productivity and keep the plant healthy. The healthy plants are simply indicated by the ratio of pecco and banji more than 2.33. This research aimed to test the effect of Mineral-Based Compound Fertilizer (CFC) on a plant health and tea plant productivity. The research was carried out in April – October 2014 at the Gambung Experimental Station, Block B6, Research Institute for Tea and Chincona by using CFC with a composition of 80% Mineral Compound Fertilizer, 10% urea, and 10% KCl. The experiments used a Randomize Blocked Design with four replications and six treatments; i.e. 120% CFC tekMIRA; 100% CFC tekMIRA; 80% CFC tekMIRA; 60% CFC tekMIRA; NPK (25:7:12:3) as control compound fertilizer; and single standard fertilizer. The result showed that all of the treatments did not increase the plant health. However, the application of CFC produced a higher tea plant productivity compared to NPK (25:7:12:3) as control compound fertilizer and single standard fertilizer. Based on regression equation, the dose of CFC that produced the optimal tea productivity was 93.92%.